Fortalecimiento Turístico al Plan de Desarrollo y Ordenamiento Territorial (PDYOT) en la parroquia Los Encuentros, cantón Yantzaza, provincia de Zamora Chinchipe. - Puglla Guaillas, Silvia Magdalena (2021)
The present research work called “Tourist Strengthening of the (PDYOT) Territorial Development and land plan in “Los Encuentros” parish, Yantzaza canton, Zamora Chinchipe province, has been proposed with the aim of improving tourist activity. The general objective of the research is to “Strengthen the Tourism Development and Territorial land Plan (PDYOT) in Los Encuentros Parish, Yantzaza Canton, Province of Zamora Chinchipe, and three specific objectives were developed: first objective: To carry out the diagnosis of the tourist component in the Los Encuentros Parish, Yantzaza Canton, Zamora Chinchipe Province; Second objective: To prepare a proposal for tourism development in the Los Encuentros parish; Third objective: Propose strategies for the application of the Tourism Development Plan in Los Encuentros Parish. To comply with the first specific objective, a brief review of the literature was carried out, confidential sources such as the PDyOT of the Los Encuentros parish, direct observation to verify the current status of the natural and cultural attractions, on-site visits, and also proceeded to raise Information where the Ricaurte worksheets were used, filling in the inventory files of tourist attractions of Mintur 2018 that helped us to obtain the ranking of tourist attractions, interviews, surveys, SWOT analysis and two participatory workshops were carried out, as well as identified that there is a deficit in terms of accommodation and recreational services, as well as there is no correct infrastructure of basic services to offer a quality service to visitors, there are 30% natural attractions and 70% cultural attractions, but currently they are in poor condition since it does not have the a corresponding decisions to carry out tourist activities, which require good planning to improve their service, with regard to the community's attitude towards tourism, positive results were obtained with more than 50% acceptance of the development of tourist activities In the communities, eight strengths, five opportunities, ten weaknesses and five threats were also obtained. From here, the strategy matrix was built. For the fulfillment of the second specific objective, it was based on the information generated from the crossed SWOT and several tourist strategies were proposed, among which the creation of a tourist product was selected as the first strategic objective, for the creation of this objective it was proposed based on the great variety of natural and cultural attractions that “Los Encuentros” parish has, as a second strategic objective the implementation of a tourist information center was proposed, a third strategic objective was raised training workshops on customer care and service and the importance of cultural identity because the actors involved in the tourist activity require constant training to provide a good service to tourists and the fourth strategic objective was the promotion of natural and cultural attractions through the social network facebook. Finally, in order to fulfill the third objective, the design of the strategies that will benefit and strengthen tourism to the PDyOT in “Los Encuentros” parish was carried out. It is concluded that “Los Encuentros” parish does not have enough service offer to satisfy visitors, basic services are of poor quality, it does not have a good infrastructure with respect to trails and tourist signs, 5 it has great tourist potential of natural attractions and cultural attractions that with their respective adaptation could improve their services. The development of tourist activities could be strengthened by giving their respective monitoring and management of the proposed projects, making agreements with other institutions that contribute to the improvement of the tourist plant, giving the respective adjustments to the tourist infrastructure, in addition to the constant training to improve the services to tourists who visit “Los Encuentros” parish. The representatives of the provincial government should consider as the main strategies for its implementation that will help to strengthen the development of tourist activities in the area.